Pharmacological evaluation of medicinal plants with antidiabetic activities in Ethiopia: A review - Zemene Demelash Kifle; Mohammedbrhan Abdelwuhab; Abreham Degu Melak; G/Mariam Genet; Tesfaye Meseret; Meaza Adugna (Metabolism Open, 2022)
Diabetes mellitus is a serious, chronic disease that occurs either when the pancreas does not produce enough insulin, or when the body can't effectively use insulin. Herbal medicines have been commonly used by diabetic patients for the treatment of diabetes mellitus. To include findings from different studies, publications related to in vivo and invitro antidiabetic activities of medicinal plants in Ethiopia were searched from different databases, such as Web of Science, Google Scholar, Medline, Scopus, and PubMed, using English key terms. Different medicinal plant parts were used experimentally for antidiabetic effects in Ethiopia. Among these, leaves (69%) were the most commonly investigated medicinal plant parts followed by roots (14%) and seeds (7%). Most of the investigations were completed with hydro-methanolic extracts to obtain a higher percentage of yield. Medicinal plants such as Thymus schemperi R, Thymus vulgaris L, Hagenia abyssinica, Aloe megalacantha baker, Aloe moticola Reyonolds, Aloe pulecherrima Gilbert & sebseb, Bersama abyssinica fresen, and Rubus Erlangeri Engl have shown in vitro α-amylase inhibitory activity. However, only Hagenia abyssinica, Thymus schemperi R, and Thymus vulgaris L have exhibited α-glucosidase inhibitory activity. Likewise, only the extract of Aloe pulecherrima Gilbert & sebseb posses’ maltase and sucrose inhibitory activity. In vivo antidiabetic activity were conducted for the extract of medicinal plants such as A. remota, S. rebaudiani, T. schemperi, T. vulgaris, H. abyssinica, C. aurea, D. stramonium, A. megalacantha, A. moticola, A.integrifolia, A. pulecherrima, B. grandiflorum, B. abyssinica, P. schimperiana, M. stenopetala, C. aure, J. schimperiana, T. brownie, C. macrostachys, I. spicata, O. integrifolia, C. abyssinica, R. Erlangeri, L. culinaris, A. camperi, A. polystachyus, A. ilicifalius, C. tomentosa, and C. Edulis. This review gives collective evidence on the potential antidiabetic activities of medicinal plants in Ethiopia. Moreover, further studies are recommended to substantiate the use of these medicinal plants as an antidiabetic agent.